2020
DOI: 10.3390/app10020529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bionic Curves on Penetration Force under Difference Soils

Abstract: Soil penetration is the most important process during soil tilling. To optimize the soil penetration process, six specimens were designed and fabricated based on the badger teeth outlines. Both experimental investigation and numerical analysis were conducted with three types of soil. Results showed the specimen C, B, and D got the lowest penetration force and reduced the force by 26.15%, 22.68%, and 25.86% compared with that of specimen A under soil 1, soil 2, and soil 3, respectively. Depth-force curve analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is noteworthy that badger teeth are extremely hard, sharp, and also have excellent cutting capabilities [ 46 ]. Ma et al [ 47 ] studied the process of badger teeth penetrating into the soil, as shown in Figure 3 d. The simulation results demonstrated that ABS-material bionic specimens designed with the badger canine outlines could change the force direction, thereby reducing the penetration resistance. Consequently, it is worth trying to use badger teeth as bionic prototypes to design low-resistance soil-engaging components.…”
Section: Biomimetic Soil-engaging Componentsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is noteworthy that badger teeth are extremely hard, sharp, and also have excellent cutting capabilities [ 46 ]. Ma et al [ 47 ] studied the process of badger teeth penetrating into the soil, as shown in Figure 3 d. The simulation results demonstrated that ABS-material bionic specimens designed with the badger canine outlines could change the force direction, thereby reducing the penetration resistance. Consequently, it is worth trying to use badger teeth as bionic prototypes to design low-resistance soil-engaging components.…”
Section: Biomimetic Soil-engaging Componentsmentioning
confidence: 99%
“… Low-resistance soil-engaging components inspired by badge claw toe/canine. ( a ) Bionic cutter teeth [ 10 ], ( b ) bionic shovel and bionic liquid fertilizer deep application spray needle [ 43 , 44 ], ( c ) biomimetic core-share furrow opener [ 48 ], ( d ) bionic curves specimens for test soil penetration resistance [ 47 ]. …”
Section: Biomimetic Soil-engaging Componentsmentioning
confidence: 99%
See 3 more Smart Citations